Chronic Dexamethasone Disturbs the Circadian Rhythm of Melatonin and Clock Genes in Goats - Liuping Cai; Qu Chen; Canfeng Hua; Liqiong Niu; Qijun Kong; Lei Wu; Yingdong Ni (Animals)
Dex is a drug commonly used as an immunosuppressive and anti-inflammatory agent in humans and animals. GCs have a profound impact on melatonin expression and biological rhythm. However, the effect of chronic exposure to Dex on melatonin secretion and biological clock gene expression in ruminants is still unclear. Ten goats were randomly divided into two groups: the control group was injected with saline, and the Dex-treated group was intramuscularly injected daily for 21 d with 0.2 mg/kg Dex. The rhythm of melatonin secretion in the plasma was disturbed in the Dex group, and the plasma and colon levels of melatonin were lower in the Dex group compared to the control group (p < 0.05). Dex leads to a significant decrease in the expression of Arylalkylamine N-acetyltransferase (AANAT), a key melatonin synthase, in the pineal gland and colon. Detecting intestinal leakage-related indices showed that diamine oxidase (DAO) and lipopolysaccharide (LPS) content increased significantly in the Dex group (p < 0.05). We also detected genes associated with biological rhythms in the plasma. In the control group, the five tested genes showed circadian rhythms, but the circadian rhythms of Clock, Cry1, Cry2, and Per2 were abolished or blunted by the Dex (p < 0.05). Protein levels of CLOCK and BMAL1 in the colon changed significantly (p < 0.05). In conclusion, the above experimental results show that chronic exposure to Dex leads to the disorder of the circadian rhythms of melatonin secretion and clock genes.